Early Childhood Education at BNCC: challenges to the consolidation of learning and development rights - José Carlos Miguel; Matheus Estevão Ferreira da Silva; Priscila Caroline Miguel (Universidade Federal do Norte do Tocantins, 2023)
This study addresses some theoretical and practical implications of the National Common Curricular Base (BNCC) for the development of pedagogical work in the field of early childhood education. Starting from an analysis of the state of the art with regard to the difficulties of teachers and students for educational action in this instance of basic education, it indicates elements for the debate that are aimed at explaining the problems listed and forwarding a process of constitution of learning subjects in early childhood education. This is a bibliographical research and documental analysis whose results show the difficulties of the basic school culture for overcoming the handling of didactic situations still strongly marked by the disregard of cultural diversity, by the association of models and by the dichotomy between caring and educating. It points to the theoretical construct of the cultural-historical perspective as a search for guidance for the realization of a broad process of production of meanings and negotiation of meanings of teaching and learning, in general, and Mathematics, in particular.